Simultaneous impact of the different water supply and year type on processing tomato yield - Bőcs, A.; Pék, Z.; Helyes, L. (International Journal of Horticultural Science, 2011)
A two year (2008 and 2009) open field experiment was conducted to study the effect of irrigation on the yield parameters and fruit components of processing tomato. Two different treatments were applied: regularly irrigated (RI), irrigation cut-off 30 days before harvest (CO), compared with unirrigated control (RF). The optimal water supply was calculated from average daily temperature. The aims of the study were to investigate the effect of different water supply on yield quantity. The regularly irrigated plant stands gave significantly higher yield, and unirrigated plants showed yield loss.Water supply had strong positive (R2=0.81) effect on marketable yield and average fruit weight (R2=0.78). Linear regression showed, that 46.5 mm more water supply caused 10 t/ha more marketable yield, and 13.4 mm more water supply caused 1 g more in the average fruit weight. The irrigation increased the Brix yield as well.